The Best Writing on Mathematics 2015, Edited by Mircea Pitici, Princeton University Press 2016, xxvi+376 pp., ISBN: 978-0-691-16965-1. - POP, Horia F. (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
This is the sixth volume in a series edited by M. Pitici and published with PUP (2010, 2011, 2012, 2013, 2014). As the other volumes it contains a collection of 27 essays (a greater number than in the previous volumes), first published in 2014, dealing with various topics of mathematics and its applications. In a consistent Introduction (12 pages) the author explains the reasons for writing these volumes and the need for the popularization of mathematics: is why each volume should be seen in conjunction with the others, part of a serialized enterprise meant to facilitate the access to and exchange of ideas concerning diverse aspects of the mathematical experience.". This introductory part contains a brief survey on the writings on mathematics - both printed and online sources.